2011
DOI: 10.1002/anie.201105565
|View full text |Cite
|
Sign up to set email alerts
|

Sticky Nanoparticles: A Platform for siRNA Delivery by a Bis(zinc(II) dipicolylamine)‐Functionalized, Self‐Assembled Nanoconjugate

Abstract: Delivering the goods: Multifunctional, self‐assembled, polymeric nanoparticles for the simultaneous delivery of small‐molecule drugs and siRNA have been synthesized. The nanoparticles are composed of biodegradable hyaluronic acid, for tumor targeting and cellular delivery, and a high siRNA binding affinity is provided by a ZnII‐dipicolylamine analogue as an artificial phosphate‐binding receptor (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 25 publications
2
73
0
Order By: Relevance
“…16,17 Second, to prepare the HDz nanocarrier, amine-functionalized bis(DPA) molecules were covalently conjugated with the carboxylic groups on the HA backbone of HA-NPs. 24 The 1 H NMR analysis indicated that 15.5 ± 3.4 molecules of CA and 28.5 ± 4.2 molecules of bis(DPA) were bound onto the HA backbone of HDz conjugate (Supporting Information Figure S2). The HDz conjugates were self-assembled in aqueous solution, forming nanosized particles with an average hydrodynamic diameter of 94.3 ± 3.5 nm (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Second, to prepare the HDz nanocarrier, amine-functionalized bis(DPA) molecules were covalently conjugated with the carboxylic groups on the HA backbone of HA-NPs. 24 The 1 H NMR analysis indicated that 15.5 ± 3.4 molecules of CA and 28.5 ± 4.2 molecules of bis(DPA) were bound onto the HA backbone of HDz conjugate (Supporting Information Figure S2). The HDz conjugates were self-assembled in aqueous solution, forming nanosized particles with an average hydrodynamic diameter of 94.3 ± 3.5 nm (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…24 Given considerably high phosphate concentration in the cell culture medium or the bloodstream, the NFs necessitate further protection from phosphate molecules in vitro and in vivo . Therefore, we added complementary calcium phosphate (CaP) layers onto the HDz/RNA-NFs by in situ mineralization of sequentially added calcium and phosphate ions.…”
mentioning
confidence: 99%
“…Here we describe a highly flexible protocol to design a sophisticated RNA carrier that we used for tumor-targeted RNA delivery in our previous studies, which is distinct from the reported gene delivery systems that are based on cationic derivatives or chemically modified RNAs 10,11 . This is an alternative RNA delivery system based on the use of Zn-DPA analog, an artificial receptor for phosphate anion derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Similar Zn-DPA analogs were also used as probes for necrotic and apoptotic cells by targeting anionic phosphatidylserine on cell surfaces 16,17 . Recently, we applied Zn-DPA analogs as carriers for the delivery of therapeutic molecules, such as siRNA, using the selective and strong binding of Zn-DPA with the phosphodiester groups on the siRNA back-bone 10,11 . In particular, this Zn-DPA platform for RNA delivery is highly flexible and can be used in conjunction with existing delivery systems such as NPs, polymers, proteins and antibodies by simply labeling the small-molecule Zn-DPA by established bioconjugation chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronan (HA), a natural polysaccharide abundant in the extracellular matrix of the body, has received increasing attention as an anticancer drug carrier because it is biocompatible and binds to the CD44 receptor, which is over-expressed in cancer cells [32][33][34][35][36][37]. Previously, it was demonstrated that the CD44 receptor is also over-expressed in the synovial tissue of RA patients [5,38], and anti-CD44 antibody has potential for the treatment of RA [39].…”
Section: Introductionmentioning
confidence: 99%